2014
DOI: 10.1002/2013jg002475
|View full text |Cite
|
Sign up to set email alerts
|

Using field data to assess model predictions of surface and ground fuel consumption by wildfire in coniferous forests of California

Abstract: Inventories of greenhouse gas (GHG) emissions from wildfire provide essential information to the state of California, USA, and other governments that have enacted emission reductions. Wildfires can release a substantial amount of GHGs and other compounds to the atmosphere, so recent increases in fire activity may be increasing GHG emissions. Quantifying wildfire emissions however can be difficult due to inherent variability in fuel loads and consumption and a lack of field data of fuel consumption by wildfire.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…For the largest Wallow fire, the biomass consumption per unit area was 3.02 kg/m 2 (Figure ), which differs by only 4% from the biomass consumption estimated using the Consume 3.0 FC model (Veraverbeke & Hook, ). The results illustrated in Figure are comparable in magnitude with biomass consumption estimates across the CONUS for different fires and years (where fuel conditions and fire behavior differences mean that exact quantitative comparison is not meaningful; Lydersen et al, ; Prichard et al, ; Yokelson et al, ).…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…For the largest Wallow fire, the biomass consumption per unit area was 3.02 kg/m 2 (Figure ), which differs by only 4% from the biomass consumption estimated using the Consume 3.0 FC model (Veraverbeke & Hook, ). The results illustrated in Figure are comparable in magnitude with biomass consumption estimates across the CONUS for different fires and years (where fuel conditions and fire behavior differences mean that exact quantitative comparison is not meaningful; Lydersen et al, ; Prichard et al, ; Yokelson et al, ).…”
Section: Resultsmentioning
confidence: 51%
“…For the largest Wallow fire, the biomass consumption per unit area was 3.02 kg/m 2 ( Figure 5), which differs by only 4% from the biomass consumption estimated using the Consume 3.0 FC model (Veraverbeke & Hook, 2013). The results illustrated in Figure 5 are comparable in magnitude with biomass consumption estimates across the CONUS for different fires and years (where fuel conditions and fire behavior differences mean that exact quantitative comparison is not meaningful; Lydersen et al, 2014;Prichard et al, 2017;Yokelson et al, 2013). Figure 6 illustrates a comparison of the biomass consumption estimated by the bottom-up method based on the burn severity parameterized CC approach with the same approach but assuming CC = 0.5 ( Figure 6a) and with the IPCC FC method (Figure 6b).…”
Section: Sensitivity Analysismentioning
confidence: 78%
“…Similarly, Lydersen et al. (2014) document total fuel consumption of ∼14 kg m −2 (140 Mg ha −1 ) in the Northern Sierra, with significant contribution from duff layers and forest litter. Large fuel consumption is also observed in other forested environments in the western US, for example, McCarley et al.…”
Section: Methodsmentioning
confidence: 86%
“…To be specific, Cansler et al (2019) found an average total fuel consumption of 15.1 kg m 2 (151 Mg ha 1 ) during the 2013 Rim Fire in Yosemite National Park. Similarly, Lydersen et al (2014) document total fuel consumption of ∼14 kg m 2 (140 Mg ha 1 ) in the Northern Sierra, with significant contribution from duff layers and forest litter. Large fuel consumption is also observed in other forested environments in the western US, for example, McCarley et al (2020) showed airborne laser scanning estimated fuel consumption in large wildfires exceeding 20 kg m 2 (200 Mg ha 1 ) over large areal expanses.…”
Section: Fuel Depiction and Fire Residence Timementioning
confidence: 91%
“…Additionally, incomplete combustion of at least one of the two litter and duff strata occurred in 74 plots (66%), with incomplete combustion of both litter and duff occurring in 44 (39%) of the 112 plots. Currently, fire consumption models such as BURNUP or FOFEM often assume high or complete combustion of litter and duff in wildfires (Lydersen et al 2014;Lutes 2020) and may therefore overestimate wildfire emissions.…”
Section: Litter Duff and 1000-h Fuels Are The Primary Contributors Of...mentioning
confidence: 99%